Bayesian soft x-ray tomography and MHD mode analysis on HL-2A. (9th February 2016) - Li, Dong; Liu, Yi; Svensson, J.; Liu, Y.Q.; Song, X.M.; Yu, L.M.; Mao, Rui; Fu, B.Z.; Deng, Wei; Yuan, B.S.; Ji, X.Q.; Xu, Yuan; et al.
Abstract: A Bayesian based tomography method using so-called Gaussian processes (GPs) for the emission model has been applied to the soft x-ray (SXR) diagnostics on HL-2A tokamak. To improve the accuracy of reconstructions, the standard GP is extended to a non-stationary version so that different smoothness between the plasma center and the edge can be taken into account in the algorithm. The uncertainty in the reconstruction arising from measurement errors and incapability can be fully analyzed by the usage of Bayesian probability theory. In this work, the SXR reconstructions by this non-stationary Gaussian processes tomography (NSGPT) method have been compared with the equilibrium magnetic flux surfaces, generally achieving a satisfactory agreement in terms of both shape and position. In addition, singular-value-decomposition (SVD) and Fast Fourier Transform (FFT) techniques have been applied for the analysis of SXR and magnetic diagnostics, in order to explore the spatial and temporal features of the saturated long-lived magnetohydrodynamics (MHD) instability induced by energetic particles during neutral beam injection (NBI) on HL-2A. The result shows that this ideal internal kink instability has a dominant m / n   =  1/1 mode structure along with a harmonics m / n   =  2/2, which are coupled near the q   =  1 surface with a rotation frequency of 12 kHz.